Of Amoebae and Men: Extracellular DNA Traps as an Ancient Cell-Intrinsic Defense Mechanism - Zhang, Xuezhi; Soldati, Thierry (Frontiers in Immunology, 2016)
Since the discovery of the formation of DNA-based Extracellular Traps (ETs) by neutrophils as an innate immune defense mechanism [1], hundreds of articles describe the involvement of ETs in physiological and pathological human and animal conditions (reviewed in [2], and the previous Frontiers Research Topic on NETosis). Interestingly, a few reports reveal that ETs can be formed by immune cells of more ancient organisms, as far back as the common ancestor of vertebrates and invertebrates [3]. Recently, we reported that the Sentinel cells of the multicellular slug of the social amoeba Dictyostelium discoideum also produce ETs to trap and kill slug-invading bacteria (See Box 1, [4]). This is a strong evidence that DNA-based cell-intrinsic defense mechanisms emerged much earlier than thought, about 1.3 billion years ago. Amazingly, using extrusion of DNA as a weapon to capture and kill uningestable microbes has its rationale. During the emergence of multicellularity, a primitive innate immune system developed in the form of a dedicated set of specialized phagocytic cells. This professionalisation of immunity allowed the evolution of sophisticated defense mechanisms including the sacrifice of a small set of cells by a mechanism related to NETosis. This altruistic behaviour likely emerged in steps, starting from the release of “dispensable” mitochondrial DNA by D. discoideum Sentinel cells. Grounded in this realisation, one can anticipate that in the near future, many more examples of the invention and finetuning of ETs by early metazoan ancestors will be identified. Consequently, it can be expected that this more complete